Robust Exact Distance Queries on Massive Networks - Delling, Daniel; Goldberg, Andrew; Pajor, Thomas; Werneck, Renato (Microsoft Technical Report, 2014)
We present a versatile and scalable algorithm for computing exact distances on real-world networks with tens of millions of arcs in real time. Unlike existing approaches, preprocessing and queries are practical on a wide variety of inputs, such as social, communication, sensor, and road networks. We achieve this by providing a unified approach based on the concept of 2-hop labels, improving upon existing methods. In particular, we introduce a fast sampling-based algorithm to order vertices by importance, as well as effective compression techniques.